1996
DOI: 10.1097/00005537-199601000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Findings in Patients with Maternally Inherited Diabetes and Deafness Harboring a Point Mutation in the Mitochondrial Transfer RNALeu (UUR) Gene

Abstract: Five patients with sensorineural hearing loss, who harbored a point mutation in the mitochondrial transfer RNA (tRNA) gene tRNA(Leu) (UUR), from five unrelated family pedigrees were examined. In these families diabetes and deafness were maternally inherited. Bilateral hearing was more severely impaired at higher frequencies. Audiometric test results revealed that hearing loss involved the cochlea. Hearing gradually deteriorated; the progression rate ranged from 1.5 to 7.9 dB per year. Proportion of mutant mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 22 publications
6
44
0
3
Order By: Relevance
“…In addition, SNHL in Japanese patients in otorhinolaryngic clinics previously reported to be due to the A3243G mutation was associated with DM (Oshima et al 1996;Tamagawa et al 1997;Usami et al 2000;Yamasoba et al 1996). The present results showed that all four patients with the mutation had family histories of maternal inheritance of SNHL, and three of the four cases were also associated with DM.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition, SNHL in Japanese patients in otorhinolaryngic clinics previously reported to be due to the A3243G mutation was associated with DM (Oshima et al 1996;Tamagawa et al 1997;Usami et al 2000;Yamasoba et al 1996). The present results showed that all four patients with the mutation had family histories of maternal inheritance of SNHL, and three of the four cases were also associated with DM.…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, it is apparent that a family history of possible Presented with SNHL and subsequently diagnosed as having glucose intolerance maternal inheritance of SNHL and association with DM are possible signs of the A3243G mutation in otorhinolaryngic clinics as well as in diabetes clinics. However, in a few cases in those previous reports, the onset of SNHL preceded that of DM (Tamagawa et al 1997;Yamasoba et al 1996), raising the possibility that these patients might have visited an otorhinolaryngic clinic before the presentation of DM. In addition, we herein report a case unassociated with DM (case 1).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Hearing loss was assessed by pure-tone audiometry. The pure tone average was calculated as the average of 0.5, 1, 2 and 4 kHz as described by Yamasoba [19]. The serum levels of CoQ 10 were determined by high-performance liquid chromatography [20].…”
Section: Methodsmentioning
confidence: 99%
“…The sensorineural hearing loss is bilateral, symmetric and originates in the cochlea. 5 This disorder is caused by an A-to-G transition at position 3243 of the mtDNA. The mutation is located in the gene encoding tRNA Leu , and results in impaired protein synthesis and electron transport chain dysfunction.…”
Section: Introductionmentioning
confidence: 99%